Geographies of Transition: Narrating environmental activism in an age of climate change and 'Peak Oil'. (January 2017) - Barr, Stewart; Pollard, Justin
The growth of community-based Transition Town initiatives in countries like the UK, USA and Canada is popularly perceived to represent a broad, socially inclusive and grounded approach to tackling environmental problems in place-based communities. In focusing on resilience as a core theme, so-called re-localisation initiatives attempt to adopt consensus based approaches to decision making and to highlight the need for an 'inner transition' of the self that encourages closer connections between individuals and nature. In this way, Transition has been framed as a new form of social and environmental movement that is re-casting community and political relations for a low carbon and post 'Peak oil' future. Yet despite these emergent philosophies of Transition and the considerable scholarship being generated on the role and success of such initiatives, there is an urgent need to situate and analyse Transition within broader understandings of environmental activism. Using data from a two year research project on 'Values in Transition', this paper argues that the praxis and spatial complexity of Transition can be understood more deeply through a narrative lens. In mobilising critical scholarship on environmental activism, the paper calls for a 'Transition Geographies' that views re-localisation as a dynamic and complex coalescence of competing narratives that sit between traditional forms of environmental activism and directive initiatives for individual behaviour change. As such, the paper highlights the ways in which this new form of environmental activism is shaping praxis across space, and the implications this has for those advocating re-localisation as a strategy for tackling climate change and resource scarcity.